Conflicted Regulators: Indirect Revolving-Door Connections in SEC Filing Reviews - Kubic, Matthew; Silva, Rui; Toynbee, Sara (The Accounting Review, 2026)
ABSTRACT We investigate whether prior employment connections influence the strictness of the Securities and Exchange Commission (SEC) filing review process. Using novel data on over 250 accountants at the SEC, we define connected examiners as accountants reviewing financial statements audited by their former employer. We find that SEC review teams with a higher percentage of connected examiners are less likely to detect financial statement errors, raise fewer substantive issues, and are less likely to push back on registrants’ responses to comment letters. Our estimates also indicate that the effect of examiners’ prior employment connections is strongest earlier in their SEC tenure and attenuates with time. Our findings provide important practical insights on the boundaries of the revolving door between regulators and the regulated, suggesting that even indirect connections can impact oversight. JEL Classifications: G18; M41; M48.